Feminism and labour supply in the Nordic countries/ Axel Hall; Gylfi Zoega - Axel Hall; Gylfi Zoega (University of Iceland, Institute of Economic Studies (IoES), 2008)
People in the Nordic countries of Denmark, Finland, Iceland and Sweden work more than the countries' high tax rates would lead us to predict. This observation is explained by a shared belief system that emphasises women's rights to labour market participation.
Keywords: 330; employment; female workers; Tax; Working hours; Denmark; Finland; Iceland; Norway; Sweden; Erwerbstätigkeit; Weibliche Arbeitskräfte; Steuer; Arbeitszeit; Dänemark; Finnland; Island; Norwegen; Schweden